2020
DOI: 10.3389/fpls.2020.01289
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Selection Traits for Effective Popcorn (Zea mays L. var. Everta) Breeding Under Water Limiting Conditions

Abstract: further root deepening in WS conditions. Under WS P7 maintained higher net photosynthesis values, stomatal conductance, and transpiration, than L75. Additionally, L75 exhibited a lower (i.e., more negative) carbon isotope composition value than P7 under WS, confirming a lower stomatal aperture in L75. In summary, besides leaf greenness, traits related to leaf photosynthetic status, and stomatal conductance were shown to be good indicators of the agronomic performance of popcorn under water constraint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 66 publications
0
21
0
Order By: Relevance
“…Grain yield and popping expansion were the traits most affected by water restriction in the soil, with reductions of 55% and 28%, respectively. According to Kamphorst et al (2020) [20], in response to WS applied during the pre-flowering and grain filling of pop-…”
Section: Effect Of Water Restriction On Gy Pe Morpho-agronomic Traits and On The Greenness Indexmentioning
confidence: 99%
“…Grain yield and popping expansion were the traits most affected by water restriction in the soil, with reductions of 55% and 28%, respectively. According to Kamphorst et al (2020) [20], in response to WS applied during the pre-flowering and grain filling of pop-…”
Section: Effect Of Water Restriction On Gy Pe Morpho-agronomic Traits and On The Greenness Indexmentioning
confidence: 99%
“…SPAD index measurements suggest a photosynthetic capacity of the leaf tissues, since that this index is correlated with chlorophyll concentration, and enable to obtain better inferences of photosynthesis [25]. Kamphorst et al (2020) [46] evaluated SPAD values popcorn inbred lines contrasted to grain yield in drought conditions. The authors showed that maximum SPAD values were obtained more later (11 days after anthesis) in WW, when compared with WS (two days after anthesis).…”
Section: Discussionmentioning
confidence: 99%
“…The authors showed that maximum SPAD values were obtained more later (11 days after anthesis) in WW, when compared with WS (two days after anthesis). Maximum SPAD index values are related to late leaf senescence, due to high chlorophyll concentration and photosynthetic carbon assimilation [46]. In addition, Gregersen (2008) [47], showed that nutrients mobilization from senescent leaves to reproductive organs are important to plant growth in drought conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Four S 7 popcorn inbred lines previously selected as water use efficient (P2 and P3, from the compound CMS-42) and inefficient (L61 and L63, from the BRS-Angela population) [ 18 , 52 ], as well as two hybrids of the cross between these four inbred lines (P2xL61 and P3xL63) were used for evaluation under different water regimes. The experiment was carried out in a greenhouse, at a research base of the State University of Norte Fluminense Darcy Ribeiro, in Campos dos Goytacazes, Rio de Janeiro, Brazil (21°45′45″ S 41°19′6″ W).…”
Section: Methodsmentioning
confidence: 99%